Design of the goat/sheep holding cage slaughtering system (cage for animal slaughter): innovations and prospect - Mat Sharif, Zainon; Syed Abdullah, Syed Nurulakla; Rahim, Mohamad Zulafif; Othman, Mohd Syafiq (Science and Engineering Research Support Society, 2019)
The main objective of inventing the goat/sheep holding cage-slaughtering mechanism or cage for animal slaughter was to seek solutions for the slaughtering mechanism from the traditional operation with four to five persons manning it to a one-person operation. The development of this innovation is for Chak Chee Bor Enterprise. This mechanism consists of a goat/sheep holding cage of 1.23m (height) X 1.60m (length) X 0.97m (width). The overall purpose of using this goat/sheep holding cage is to keep the goat/sheep calm, whilst minimizing the danger of unnecessary injury to both the animal and worker. The goat/sheep holding cage-slaughtering mechanism consists of a head latch (neck yoke or head gate) to hold the animal‘s neck and head, and two wooden boards to hold or gently clamp the body of the animal, with the purpose to calm the animal and ensure that it does not move. The round-shaped iron pieces at the end of both sides of the holding cage enable the mechanism to be swung aside or tilted at a 45o angle before the final stage of the ritual. This holding cage-slaughtering mechanism that comes with an adjustable head latch is able to accommodate different sizes of animals.